Burden of Teenage Pregnancies in Hilly Area of Eastern Region of Nepal - Sah, Ram Bilakshan; Gaurav, Kumar; Baral, Dharani Dhar; Jha, Nilambar; Pokharel, Paras Kumar (Journal of Nobel Medical College, 2015)
Teenage pregnancy, which is detrimental to the health of mother and child, is a common public health problem worldwide. It is a problem that affects nearly every society- developed and developing alike. The objective of this study was to find out the prevalence of teenage pregnancy and its impact on birth outcome. The cross-sectional study was conducted among the residents of Dhankuta municipality where 246 households were taken as subjects. Chi-square test was applied to find out the significant difference between socio demographic characteristics and outcome variable i.e. birth outcome & age of 1st pregnancy. About 34.6% of respondents were pregnant at below 20 years of age. The teenage pregnancies decreases as education level increases (p<0.001). Furthermore, economic variable shows stronger association with teenage pregnancies (p<0.001). Fetal complication was significantly higher among below 20 years of age (81%) than women with 20 years and above (19%). The proportion of low birth weight (<2.5 kg) babies was also significantly higher in women with teenage pregnancy (78.3%) than women with 20 years and above (21.7%). We conclude that the problem of teenage pregnancy is common and has become a key public health concern for all. The teenage pregnancy was not favorable condition for baby outcome. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.12231 Journal of Nobel Medical College Vol. 3, No.1 Issue 6, 2014, Page: 13-19